Strengthening Students' 21st-Century Skills Through the Friday Tausiyah Program at Telukjambe Islamic Middle School - Nurul Azkiya; Achmad Junaedi Sitika; Nurhasan (al-Afkar, Journal For Islamic Studies, 2025)
In the current era of digital and globalization, very few teenagers have mastered communication skills, therefore, this problem cannot be ignored. In this case, an effort is needed to overcome it. One of them is that students' 21st century communication skills are very important for students at school, one of which is through Friday tausiyah activities. Friday Tausiyah is a religious activity at Telukjambe Islamic Middle School, which is held every Friday. The purpose of this research is to determine the planning of the Friday Tausiyah program on students' 21st century skills at Telukjambe Islamic Middle School. To find out the implementation of the Friday Tausiyah program at Telukjambe Islamic Middle School on students' 21st century skills. To find out the results achieved in strengthening students' 21st century skills. through the Friday tausiyah program at Telukjambe Islamic Middle School. This research method uses a qualitative approach with descriptive research type. This research was conducted at Telukjambe Islamic Middle School, data collection, researchers used observation, interviews and documentation methods. Meanwhile, for the analysis, researchers used descriptive analysis, namely in the form of data reduction, data presentation and verification. The results of this research reveal that, (1) The planning of the Friday Tausiyah program for students' 21st century skills is what sparked the formation of the Friday Tausiyah program, namely the school principal and forming a religious team so that this activity could be implemented. (2) The implementation of Friday tausiyah in developing students' communication skills has been well pursued by the religious team and the school. (3) The results achieved in mastering students' 21st century skills are that students have more control over the stage, are brave and confident to speak in public.